2022
DOI: 10.3390/ma15248789
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Properties of Carbon Fiber-Reinforced PEEK against 304 Stainless Steel with Reticulate Surface Texture

Abstract: With the aim of improving the durability and reliability of polyetheretherketone (PEEK) composites reinforced with carbon fiber (CF) as thrust bearings without lubricants, a reticulate surface texture was fabricated by plane honing on a stainless steel (SS) counterpart to promote its tribological properties. Pin-on-disk experiments were designed, with the results showing that the reticulate surface texture effectively reduces the friction coefficient from 0.40 to 0.20 compared with the polished SS surface, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…When the textured samples were corroded by hydrochloric acid solution, the surface friction coefficient is the lowest. It is indicated that acid corrosion effect is must existed for the interfacial tribological properties (Meng et al , 2019; Jin et al , 2022).…”
Section: Results and Analysismentioning
confidence: 99%
“…When the textured samples were corroded by hydrochloric acid solution, the surface friction coefficient is the lowest. It is indicated that acid corrosion effect is must existed for the interfacial tribological properties (Meng et al , 2019; Jin et al , 2022).…”
Section: Results and Analysismentioning
confidence: 99%
“…Abrasive wear is caused by particulate matter, such as hard particles or surface impurities, entering the bearing and generating a cutting action, resulting in grooves and scratches on the bearing surface [37]. Fatigue wear results from pitting and spalling on the bearing surface due to excessive pressure and high rotational speeds inside the bearing [38]. Oxidative wear is caused by high temperatures and oxidation reactions that cause oxidation and spalling on the bearing surface [39].…”
Section: Main Forms Of Wear On Wind Power Bearingsmentioning
confidence: 99%